Pengaruh Media Video Animasi terhadap Kemampuan Keaksaraan dan Berpikir Simbolik Anak TK - Anggraeni, Stefanni Okta; Bachri, Bachtiar Syaiful; Jannah, Miftakhul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of animated video media on literacy and symbolic thinking abilities of group A children in Aisyiyah Kindergarten, Ngunut Tulungagung District. This research was conducted using a quasi-experimental design through a quantitative approach. The experimental design used is a nonequivalent control group design. The research subjects were group A children of TK Aisyiyah Bustanul Athfal 3 Ngunut and TK Aisyiyah Pulosari, with a total of 30 children in the experimental group and 30 children in the control group. The data analysis technique in this study used non-parametric statistics, the Mann Whitney test. The results of the study, there are differences in the average value of literacy skills. The average value of literacy ability of the experimental group at the time of the pretest was 1.58 and after being given treatment, the posttest average value of 3.30. While the average value of the ability to recognize patterns in the control group during the pretest was 1.54 and after being treated, the posttest was 2.55. In conclusion, there is an effect of animated video media on children's literacy skills and there is an influence of animated video media on the symbolic thinking ability of group A children in Aisyiyah Kindergarten, Ngunut Tulungagung District. Keywords: Literacy Ability, Symbolic Thinking Ability, Animated Video Media